Answer:
A
Step-by-step explanation:
using the rule :
=
+ 7
sequence A with a₁ = 11
a₂ = a₁ + 7 = 11 + 7 = 18
a₃ = a₂ + 7 = 18 + 7 = 25
a₄ = a₃ + 7 = 25 + 7 = 32
sequence A is generated using the rule
sequence B with a₁ = 17
a₂ = a₁ + 7 = 17 + 7 = 24
a₃ = a₂ + 7 = 24 + 7 = 31
a₄ = a₃ + 7 = 31 + 7 = 38
sequence B is not generated using the rule
sequence C with a₁ = - 15
a₂ = - 15 + 7 = - 8
a₃ = a₂ + 7 = - 8 + 7 = - 1
a₄ = a₃ + 7 = - 1 + 7 = 6
sequence C is not generated using the rule
sequence D with a₁ = - 9
a₂ = a₁ + 7 = - 9 + 7 = - 2
a₃ = a₂ + 7 = - 2 + 7 = 5
a₄ = a₃ + 7 = 5 + 7 = 12
sequence D is not generated using the rule

Subtract 3 from both sides,

Let x = X and y - 3 = Y
Then,

So, we have shifted the origin to a point (0, 3).
This is an odd function and the graph of an odd function is symmetrical about the origin.
That is, symmetrical about X = 0, Y = 0
Symmetrical about x = 0,, y - 3 = 0
Symmetrical about x = 0, y = 3.
Hence, the graph is symmetrical about the point (0, 3).
They must have the same variable with the same exponent. The coefficient doesn't matter much.
Answer:
The highest altitude that the object reaches is 576 feet.
Step-by-step explanation:
The maximum altitude reached by the object can be found by using the first and second derivatives of the given function. (First and Second Derivative Tests). Let be
, the first and second derivatives are, respectively:
First Derivative

Second Derivative

Then, the First and Second Derivative Test can be performed as follows. Let equalize the first derivative to zero and solve the resultant expression:


(Critical value)
The second derivative of the second-order polynomial presented above is a constant function and a negative number, which means that critical values leads to an absolute maximum, that is, the highest altitude reached by the object. Then, let is evaluate the function at the critical value:


The highest altitude that the object reaches is 576 feet.
-4 = 3x + 6y
6y = -3x - 4
y = -1/2x - 2/3.....slope here is -1/2. A parallel line will have the same slope
ax - 8y = 12
-8y = -ax + 12
y = (-a/-8)x + 12......so a would have to be -4 because -(-4) / -8 = -4/8 = -1/2
ur answer is : a = -4